Case report: Reactive Epstein–Barr virus-associated hemophagocytic lymphohistiocytosis and thrombosis with thrombocytopenia syndrome following SARS-CoV-2 vaccination and treated with intravenous immunoglobulin - Chang, Yueh-Shih; Ye, Jung-Jr; Cheng, Tzu-Chien; Wen, Ying-Hao; Huang, Chi-Ying F.; Yeh, Kun-Yun (Frontiers in Hematology, 2022)
Viral reactivation was previously reported after severe acute respiratory syndrome coronavirus‐2 (SARS-CoV-2) infection but was seldom documented after SARS-CoV-2 vaccination, except varicella-zoster virus and cytomegalovirus. Here, we present a case of reactive Epstein–Barr virus (EBV)-associated hemophagocytic lymphohistiocytosis (HLH) and thrombosis with thrombocytopenia syndrome after receiving SARS-CoV-2 mRNA vaccination. Antiplatelet factor 4 antibody was detected, and the bone marrow study showed hemophagocytosis and was positive in the immunohistochemistry staining for EBV-encoded small nuclear RNAs and negative staining for CD3 and CD56 markers of small lymphocytes. The high percentage of CD38 high/HLA-DR+ cells among CD8+ T cells further confirmed HLH. After intravenous administration of immunoglobulin, the clinical symptoms, D-dimer level, fibrinogen, platelet count, EBV-DNA titer, and anti-PF4 level were all improved. Further investigation into the pathogenesis of vaccine-associated EBV reactivation is warranted.